Distribución de roedores sigmodontinos (Rodentia: Cricetidae) en pastizales de neblina del noroeste de Argentina - Jayat, Jorge Pablo (2008)
Distribution of sigmodontine rodents (Rodentia: Cricetidae) in the cloud highland grasslands of Northwestern Argentina. The sigmodontine rodents community of cloud highland grasslands of Northwestern Argentina is reported based on records obtained by trapping, analyses of owl pellets, study of museum specimens and literature. We recorded 34 species for this environment in Argentina, which is dominated by the Tribes Akodontini and Phyllotini. The Tribes Abrothrichini, Oryzomyini and Reithrodontini are poorly represented and two incertae sedis species complete this assemblage. Only Necromys lactens and Phyllotis osilae are characteristic elements of this environment and their ecotonal areas. Akodon boliviensis, A. lutescens, A. simulator, A. spegazzinii, A. sylvanus, Necromys lasiurus, Oxymycterus paramensis, Oligoryzomys sp., Oligoryzomys cf. O. flavescens, Calomys fecundus, C. lepidus, C. musculinus, Andinomys edax and Neotomys ebriosus present at least one record in pure cloud highland grasslands. Necromys amoenus, Graomys edithae, G. griseoflavus, Phyllotis caprinus and Tapecomys wolffsohnii are found only in the ecotone with high Andean environments. Abrothrix illuteus, Akodon aliquantulus, A. budini, A. fumeus, Necromys sp., Oxymycterus sp. and Phyllotis anitae were recorded only in the ecotone with Chaco and Yungas forest at lower altitude. Finally, Oligoryzomys chacoensis, Calomys laucha and Eligmodontia moreni were considered dubious for this environment. The sigmodontines community of cloud highland grasslands shows a latitudinal turnover, with Akodon boliviensis, A. budini, A. fumeus, A. sylvanus, Necromys amoenus, Phyllotis caprinus y Tapecomys wolffsohnii restricted to northernmost region, and Abrothrix andinus, A. illuteus, Akodon aliquantulus, Calomys fecundus, Graomys edithae, G. griseoflavus, Necromys lasiurus, Necromys sp., Oxymycterus sp., Reithrodon auritus and Phyllotis anitae distributed only in the south of the study area. Recent additions to the sigmodontine fauna of this region indicate that more work is needed to reach an adequate picture of the diversity and distribution for this group in this environment.